PENGARUH HARGA SEWA, KUALITAS PELAYANAN, DAN CITRA MEREK TERHADAP KEPUASAN KONSUMEN PADA PO KENSYA TRANS - Mardani Setiawan; Marsi Fella Rizki (POLITEKNIK LP3I JAKARTA, 2025)
The aim of this research is to determine the effect of price, service quality and brand image on consumer satisfaction. This research uses a quantitative approach with a population of PO Kensya Trans consumers in October of 3995 people. In this research the sample was selected using the Slovin formula and obtained a research sample of 97.5 rounded up to 100 samples. Data collection uses a questionnaire. Data analysis was carried out using WarpPLS 8.0 software by analyzing convergent validity tests, discriminant validity tests, reliability tests, model fit tests, r2 tests, q2 tests and hypothesis tests. The test results show that the price variable does not have a positive and significant effect, then the service quality and brand image variables show that the results have a positive and significant effect.